LIFESTYLE GENERASI MILLENIAL DALAM KERANGKA PASAR EKONOMI HALAL - Ning Purnama Sariati (Istithmar: Jurnal Studi Ekonomi Syariah, 2019)
Lifestyle is human behavior on activities, interest and opinion in the society. Millennial generation is person who was born on periode among 1980 until 2000 and get use technology integration on the whole life. Milenial generation in this moment has different characters than other generation. Its generation so fast in the mastery of knowledge, critical, closer with social media, productive, dynamic, and open minded. Based on those character, milenial generation is predicted to contribute in the economic development. Halal economic market is about Islamic economis that support by halal industry Sektor such ac halal food, halal tourism, halal cosmetics, halal finance, halal media and recreation, halal farmation and moslem fashion. To develop this industry, government made the halal regulation and choosed the related institution. Halal economic market is new issue in the global economic. It was conduct the people to have a halal lifestyle. It means that halal economic market is not only about moslem but also about non moslem. Important thing in this case is people awareness on the halal concept in the product and service to fulfill human need. This research method is descriptive analytics research method. It use a secondary data. The are government report of KPPA 2018, islamic economic report, masterplan syariah economic of Indonesia 2019-2024, and others documents related. This research was described that lifestyle of millennial generation in Indonesia has contribute in the halal economic market’s development. Because Indonesia has many supporting aspect in this case. Indonesia has about 250 million peoples, Islam majority in religion, has surplus on millennial generation, on going to disruption era. This country must be lead to use the millennial generation for taking participant in this economic Sektor.